World theories of theatre - Odom, Glenn 1975- (Milton Park, Abingdon, Oxon Routledge, 2017)
"World Theories of Theatre expands the horizons of theatrical theory beyond the West, providing the tools essential for a truly global approach to theatre. Identifying major debates in theatrical theory from around the world, combining discussions of the key theoretical questions facing theatre studies with extended excerpts from primary materials, specific primary materials, case studies and coverage of Southern Africa, the Caribbean, North Africa and the Middle East, Oceania, Latin America, East Asia, and India"--Provided by publisher.
Introduction: World, Theory, Theatre -- Part 1: Theoretical Questions -- Part 2: Cultural and Literary Theory -- Theory and Practice -- Bibliography.
Includes bibliographical references and index.
Keywords: Theater -- Philosophy